Psychometric properties of the Healthy and Unhealthy Eating Behavior Scale (HUEBS) among Indonesian college students based on the Rasch model - Pratiwi, Trisasanti Mega; Srisayekti, Wilis; Devy Kumalasari, Asteria; Muliadi, Rahmad (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Eating behavior is a crucial aspect of human life, encompassing multiple dimensions. Unfortunately, no Indonesian-language instrument is specifically designed to measure healthy and unhealthy eating behaviors. This study aimed to evaluate the validity and reliability of the Indonesian version of the Healthy and Unhealthy Eating Behavior Scale (HUEBS) among 210 first-year undergraduate students. The data collection used a random sampling technique among first-year university students in one of the private universities in Indonesia. The HUEBS consists of two subscales: healthy eating behavior and unhealthy eating behavior. The Rasch model was employed to examine the scale's psychometric properties, including unidimensional, rating scale functioning, item fit, and differential item functioning (DIF). The results indicated that all items met the recommended fit criteria (infit and outfit MNSQ) and demonstrated adequate point-measure correlations (> 0.30). The 7-point rating scale functioned optimally and consistently. Item and person reliability values (.99 and .85–.86, respectively) were categorized as good to excellent, supporting the scale’s sensitivity in distinguishing levels of eating behavior. The results show that HUEBS can measure healthy eating and unhealthy eating behavior among university students and can be used as a basis for intervention related to lifestyle.Perilaku makan merupakan aspek penting dalam kehidupan manusia. Namun, hingga saat ini belum tersedia instrumen berbahasa Indonesia yang secara khusus dirancang untuk mengukur perilaku makan sehat dan tidak sehat. Penelitian ini bertujuan untuk mengevaluasi validitas dan reliabilitas versi Indonesia dari Healthy and Unhealthy Eating Behavior Scale (HUEBS) pada 210 mahasiswa sarjana tahun pertama. Pengumpulan data dilakukan dengan menggunakan teknik random sampling pada mahasiswa tahun pertama di salah satu universitas swasta di Indonesia. HUEBS terdiri atas dua subskala, yaitu perilaku makan sehat dan perilaku makan tidak sehat. Model Rasch digunakan untuk menguji karakteristik psikometris skala, meliputi unidimensionalitas, fungsi skala penilaian, item fit, serta differential item functioning (DIF). Hasil penelitian menunjukkan bahwa seluruh butir memenuhi kriteria kelayakan (infit dan outfit MNSQ) serta memiliki korelasi point-measure yang memadai (> 0,30). Skala penilaian 7 poin berfungsi secara optimal dan konsisten. Nilai reliabilitas butir (.99) maupun reliabilitas responden (.85–.86) termasuk dalam kategori baik hingga sangat baik, sehingga mendukung sensitivitas skala dalam membedakan tingkat perilaku makan. Dengan demikian, HUEBS terbukti mampu mengukur perilaku makan sehat dan tidak sehat pada mahasiswa, serta dapat dijadikan dasar bagi pengembangan intervensi terkait gaya hidup.